Variants of PEAR1 Are Associated With Outcome in Patients With ACS and Stable CAD Undergoing PCI - Stimpfle, Fabian; Bauer, Maike; Rath, Dominik; Schaeffeler, Elke; Schwab, Matthias; Gawaz, Meinrad; Winter, Stefan; Geisler, Tobias (Frontiers in Pharmacology, 2018)
Introduction: Platelet endothelial aggregation receptor 1 (PEAR1) triggers platelet aggregation and is expressed in platelets and endothelial cells. Genome-wide association studies (GWAS) showed an association between platelet function and single-nucleotide polymorphisms (SNPs) in PEAR1. Methods: In 582 consecutive patients with stable coronary artery disease (CAD) or acute coronary syndrome (ACS) scheduled for PCI and treated with ASA and Clopidogrel, Prasugrel, or Ticagrelor, SNP analysis for rs12566888, rs2768759, rs41273215, rs3737224, and rs822442 was performed. During a follow-up period of 365 days after initial PCI, all patients were tracked for a primary endpoint, defined as a combined endpoint consisting of either time to death, myocardial infarction (MI) or ischemic stroke. All cause mortality, MI and ischemic stroke were defined as secondary endpoints. Results: Multivariable Cox model analysis for the primary endpoint revealed a significantly increased risk in homozygous PEAR1 rs2768759 minor allele carriers (hazard ratio, 3.16; 95% confidence interval, 1.4–7.13, p = 0.006). Moreover, PEAR1 rs12566888 minor allele carriers also showed an increased risk in all patients (hazard ratio, 1.69; 95% confidence interval, 0.87–3.27, p = 0.122), which was marginally significant in male patients (hazard ratio, 2.12; 95% confidence interval, 1.02–4.43, p = 0.045; n = 425). Conclusions: To the best of our knowledge, this is the first study showing that distinct genetic variants of PEAR1 are associated with cardiovascular prognosis in high risk patients undergoing PCI and treated with dual anti platelet therapy.